Densidade do coberto vegetal na casta Alfrocheiro (Vitis vinifera) 1. Efeitos na estrutura e microclima do coberto vegetal, vigor e expressão vegetativa - Botelho, Manuel (2012)
The evaluation of shoot density and basal leaf removal effects on canopy structure, canopy microclimate and on vigour and vegetative growth was carried out during 3 years (2004 to 2006) on ‘Alfrocheiro’ vine variety, at Dão Delimited Region, Center-North of Portugal. Three different shoot densities were assayed (at G stage of Baggiolini scale): control (D1), 18 shoots.m-1 row (D2) and 12 shoots.m-1 row (D3). At veraison, leaf removal was introduced at fruit zone – F1 (no leaf removal - F0). In any of the years were found signifi cant differences between the different treatments, in terms of ecophysiological behaviour, however, between the three years signifi cant differences in the seasonal evolution of predawn leaf water potential were observed, mostly explained by meteorological conditions, mainly the amount and distribution of rainfall during the growing season. The vegetative growth was largely marked by year, especially by rainfall. In 2005, the growth of lateral shoots, due to the strong water stress observed, was reduced and, as a consequence, the total leaf area per plant was lower than in 2004 and 2006. In any year, the differences in total leaf area per plant were due to the number of shoots, since the leaf area per shoot was equal. The shoot weight was increased proportionally to the reduction of its number, while no signifi cant differences in pruning weight per vine were found. Shoot thinning resulted in a reduction of the canopy density at cluster zone, fewer leaf layer number and increased light interception. Similar but more pronounced effects were obtained by leaf removal. At the upper part of canopy, although minor variations were observed between different shoot densities, in none of them were observed shade conditions which have led to situations of leaf senescence by lack of sunlight.